PEMBERDAYAAN UMKM PEDAGANG KAKI LIMA DI SEKITAR KAMPUS KOTA SERANG MELALUI PENDAMPINGAN MANAJEMEN USAHA - Asfar, Andi Hasryningsih; Tabroni, Tabroni; Surachman, Surachman; Harsono, Pramudi; Salapudin, Salapudin; Sukmawan, Irwan (Indonesian Collaboration Journal of Community Services (ICJCS), 2025)
This community service activity aims to empower micro, small, and medium enterprises (MSMEs), particularly street vendors operating around university areas in Serang City, through business management assistance. Street vendors play a significant role in supporting local economic activities; however, many of them still manage their businesses in a traditional manner with limited managerial skills, especially in financial management and business planning. The activity was conducted using a participatory and practice-based approach, involving stages of initial needs assessment, business management training, on-site mentoring, and evaluation. The program was implemented over one month in September 2025 and involved street vendors from various business sectors. The results indicate a significant improvement in participants’ understanding of basic business management, including simple financial record-keeping, capital management, and pricing strategies. In addition to increased knowledge, behavioral changes were observed, particularly in the adoption of daily transaction records and the separation of business and personal finances. The campus environment provided a strategic context due to stable market demand and close interaction with the academic community. Overall, the activity demonstrates that continuous and contextual business management assistance can effectively enhance the capacity, independence, and sustainability of street vendor MSMEs. The program also highlights the role of higher education institutions in strengthening local economic development through community-based empowerment initiatives.